(untitled) (FAVE Sección Ciencias Veterinarias, 2021)
The aim of this work was to analyze the presence of genes associated with the virulence of thermotolerant Campylobacter (CT) isolated from different sources in commercial broiler farms. For this, we worked with a collection of CT isolates obtained from three commercial broiler farms during 2015. The presence of 10 genes related to CT virulence was examined with a PCR reaction. The results showed a prevalence of 100% for flaA and flhA; 91% cadF, 51% cdtABC, 48% iam, 46% racR, 32% ciaB and 11% virB11. C. jejuni showed higher prevalence of all genes evaluated than C. coli, except iam and virB11 wich were higher for C. coli. The same gene pattern was presented in different sources of isolates. The high prevalence of flaA and flhA, involved in CT mobility, cadF related to Campylobacter gut colonization of broiler and cdtABC genes involved for the expression of cytotoxin, indicates the importance of these factors in CT virulence. Differences in the prevalence of genes according to the species of CT could demonstrate different mechanisms of pathogenicity, and this is not related to the source of isolates. All the results showed the ability of CT to colonize cells but is not evidence of pathogenesis.